Broth versus Surface-Grown Cells: Differential Regulation of RsmY/Z Small RNAs in Pseudomonas aeruginosa by the Gac/HptB System - Jean-Pierre, Fabrice; Tremblay, Julien; Déziel, Eric (Frontiers in Microbiology, 2017)
Two-component systems are capable of profoundly affecting genetic regulation in bacteria by detecting environmental stimuli, allowing them to quickly adapt. In Pseudomonas aeruginosa, the small RNAs (sRNAs) RsmY and RsmZ are under the control of the GacS/A system. They have been described as ones of the major key players in the control of planktonic and surface-associated behaviors. Genetic regulation by these sRNAs is achieved by the titration of the negative post-transcriptional regulator RsmA which affects the expression of over 500 genes. There is increasing evidence pinpointing the importance of RsmY and RsmZ in the planktonic-sessile P. aeruginosa lifestyles switch control. Using swarming motility as a model, we show here that these sRNA are differentially regulated depending on the selected growth conditions (i.e. planktonic versus surface grown-cells). Also, we report that in contrast to planktonically-grown cells, rsmZ regulation does not implicate the response regulator GacA in swarming cells. Furthermore, we present data indicating that RsmY/Z expression influence swarming motility via the protein HptB which acts as a negative regulator of these sRNAs and that they do not strictly converge to RsmA as previously reported.